Tensile and shear bond strengths of composite bonding systems on etched enamel contaminated by saliva - Ortega, Catherine T.; Santos, Eliruth B.; Start, Precious C.; Uy, Henry G.
The objectives of the study are to determine the tensile and shear bond strengths of different restorative bonding systems on etched enamel exposed to saliva 3.2 extracted human mandibular molars were each prepared with a cavity with dimension of 5 x 3 x 1.5 mm and, after which, etched with 34% orthophosphoric acid for 30 seconds. 16 of these were soaked in saliva for 2 minutes. All teeth then rinsed and air-dried. The bonding agents of the systems were then applied on saliva contaminated and uncontaminated samples. Prior to condensation and incremental curing of the composite in each cavity preparation 4 inches gauge. .28 stainless steel wire was inserted to be attached to the testing machine. After curing, the samples were then mounted into the testing machine. For the SEM study, 10 extracted human incisors were etched with 34 % orthophosphoric acid on the labial surface. The teeth were sectioned in the midline resulting to left and right halves. The right halves were then soaked in fresh saliva for 2 minutes, rinsed and air-dried and together with the left halves, were mounted on the scanning eletron microscope for investigation.
Results showed that Tetric had the highest tensile bond strength (1465 psi) in etched enamel uncontaminated by saliva, while Polofil had the highest shear bond strength in uncontaminated samples (1577 psi). Scanning electron microscopic study revealed presence of organic and crystal layers blocking the porosities in saliva-contaminated samples.
Keywords: Composites; Saliva contamination